2020
DOI: 10.1161/hcq.13.suppl_1.209
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 209: Prevalence and Prognostic Significance of Aortic Stenosis in Patients With Acute Decompensated Heart Failure: The Atherosclerosis Risk in Communities Study

Abstract: Background: Heart failure (HF) patients with aortic stenosis (AS) constitute a high-risk population posing diagnostic and therapeutic challenges. Few studies have characterized the burden of AS in patients admitted with acute decompensated HF (ADHF), stratified by ejection fraction (EF). Methods: The Atherosclerosis Risk in Communities study conducted community-based surveillance of a random sample of ADHF hospitalizations for residents ≥55 years of age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The model is enabled by two implantable soft robotic sleeves; an LV sleeve that re‐creates the loss of LV compliance characteristic of HFpEF, and an aortic sleeve that can recapitulate changes in the afterload associated with aortic stenosis, often leading to HFpEF ( Figure A). [ 51 ] In previous studies, we demonstrated the ability of the LV sleeve to limit cardiac filling in an in vitro model of aortic stenosis and that of the aortic sleeve to recreate the hemodynamics of pressure overload in vitro and in vivo. [ 52,53 ] Here, we redesign the LV sleeve for the development of a porcine model of HFpEF capable of tuning pressure overload and ventricular compliance independently, in a facile, immediate, tunable manner, which allows us to re‐create a broad spectrum of HFpEF hemodynamics.…”
Section: Introductionmentioning
confidence: 99%
“…The model is enabled by two implantable soft robotic sleeves; an LV sleeve that re‐creates the loss of LV compliance characteristic of HFpEF, and an aortic sleeve that can recapitulate changes in the afterload associated with aortic stenosis, often leading to HFpEF ( Figure A). [ 51 ] In previous studies, we demonstrated the ability of the LV sleeve to limit cardiac filling in an in vitro model of aortic stenosis and that of the aortic sleeve to recreate the hemodynamics of pressure overload in vitro and in vivo. [ 52,53 ] Here, we redesign the LV sleeve for the development of a porcine model of HFpEF capable of tuning pressure overload and ventricular compliance independently, in a facile, immediate, tunable manner, which allows us to re‐create a broad spectrum of HFpEF hemodynamics.…”
Section: Introductionmentioning
confidence: 99%